2018
DOI: 10.3390/s18030800
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensor for Bilirubin Detection Using Screen Printed Electrodes Functionalized with Carbon Nanotubes and Graphene

Abstract: Practice oriented point-of-care diagnostics require easy-to-handle, miniaturized, and low-cost analytical tools. In a novel approach, screen printed carbon electrodes (SPEs), which were functionalized with nanomaterials, are employed for selective measurements of bilirubin, which is an important biomarker for jaundice. Multi-walled carbon nanotubes (MWCNT) and graphene separately deposited on SPEs provide the core of an electrochemical sensor for bilirubin. The electrocatalytic activity towards bilirubin oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…The separate deposition of graphene and multi-walled carbon nanotubes (MWCNT) on screen-printed carbon electrodes (SPE) offersthe electrochemical sensor core for the detection of bilirubin and is evaluated for electroanalytical parameters, such as higher sensitivity, wider linear range and lower detection limit. The data suggested that SPE-based bilirubin sensors can beessential for the management of healthcare and can be used for care diagnosis [ 67 ].…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%
“…The separate deposition of graphene and multi-walled carbon nanotubes (MWCNT) on screen-printed carbon electrodes (SPE) offersthe electrochemical sensor core for the detection of bilirubin and is evaluated for electroanalytical parameters, such as higher sensitivity, wider linear range and lower detection limit. The data suggested that SPE-based bilirubin sensors can beessential for the management of healthcare and can be used for care diagnosis [ 67 ].…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%
“…Graphene oxide were electrochemically reduced to the SPE surface. Better electroanalytical parameters have been recorded in the case of SPE modified with graphene, explained by a more enhanced electron transfer rate and a higher surface area calculated by electrochemical measurements [ 232 ]. A paper-based sensor was fabricated using graphene and carbon ink for the WE printing.…”
Section: Metal Nanoparticles and Carbon-based Nanomaterials In (Bio)sensors Designmentioning
confidence: 99%
“…Electrochemical detection of clinically important biomarkers using non-enzymatic electrodes fabricated using graphene-based nanomaterials is an another important application. Thangamuthu et al developed a non-enzymatic sensor for bilirubin detection, an important biomarker of jaundice, using ErGO [42]. In a screen-printed carbon electrode, ErGO was functionalized and its electrochemical activity towards bilirubin was comparatively studied with MWCNT functionalized electrode.…”
Section: Graphene/graphene Oxide Nanomaterials Based Electrochemicmentioning
confidence: 99%
“…( C ) CV profiles of the MGNF electrodes in the solution of 50 mM, pH 7.0 PBS with 1 mM AA, 0.1 mM DA, and 0.1 mM UA. Figures reproduced with permission from: ( A ) [42], MDPI © ; ( B ) [104], Elsevier © ; and ( C ) [105], Wiley Interscience © .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation